Optimized Stem Cell Detection Using the DyeCycle-Triggered Side Population Phenotype - Maximilian Boesch; Dominik Wolf; Sieghart Sopper (Hindawi Limited, 2016)
Tissue and cancer stem cells are highly attractive target populations for regenerative medicine and novel potentially curative anticancer therapeutics. In order to get a better understanding of stem cell biology and function, it is essential to reproducibly identify these stem cells from biological samples for subsequent characterization or isolation. ABC drug transporter expression is a hallmark of stem cells. This is utilized to identify (cancer) stem cells by exploiting their dye extrusion properties, which is referred to as the "side population assay." Initially described for high-end flow cytometers equipped with ultraviolet lasers, this technique is now also amenable for a broader scientific community, owing to the increasing availability of violet laser-furnished cytometers and the advent of DyeCycle Violet (DCV). Here, we describe important technical aspects of the DCV-based side population assay and discuss potential pitfalls and caveats helping scientists to establish a valid and reproducible DCV-based side population assay. In addition, we investigate the suitability of blue laser-excitable DyeCycle dyes for side population detection. This knowledge will help to improve and standardize detection and isolation of stem cells based on their expression of ABC drug transporters.